(untitled) (Management and Connections Journal, 2026)
Grounded in Connectivism Theory Siemens (2004), this study investigates how private higher education institutions in the state of Pará, Brazil, are incorporating new technologies into Business Administration curricula, based on insights from academic program coordinators. The theoretical framework addresses technology-enhanced professional education and the application of connectivist principles in curriculum design. This qualitative, exploratory study employs a case study methodology, drawing on data from the Foundation for the Coordination of Improvement of Higher Education Personnel Theses and Dissertations Portal, Scopus, and Scielo. Semi-structured interviews were conducted with coordinators from selected private institutions. Data analysis was performed using Content Analysis techniques, supported by the Atlas.ti software. Findings indicate institutional efforts toward technological advancement through training courses, workshops, and collaborative partnerships. Nevertheless, challenges persist in terms of curriculum modernization and faculty development, which in turn affect student autonomy and the overall effectiveness of training for engagement in immersive digital environments.